Critical Post-Functionalism in the Architecture of Late Soviet Central Asia - Igor Demchenko (ABE Journal)
Relying on all but forgotten texts of architectural criticism from late Soviet Central Asia, the article explores the discursive strategies employed by architects, critics, and historians to justify the shift away from the rigid functionalism of the 1960s to the regionally sensitive architecture of the 1970s and the 1980s. Soviet architects and critics, alert to the Soviet government’s insistence on the primordial continuity of regional and ethnic architectural traditions, and to the need to incorporate them into the new socialist style of Central Asian architecture, used the ideological quest for national forms as a means of expressing their growing distrust of prefabricated functionalism and their opposition to a Central Asian version of the Stalinist style. This architectural criticism essentially shielded late Soviet architecture from ideological dogma, allowing for its impressive formal flexibility. By critically exploring two scholastic distinctions, first between the national form and the socialist content (or essence), and second between the national and the international in socialist architecture, this article reconstructs the unique intellectual conditions governing the architectural profession in the USSR where architects operated in a context characterized by the impossibility of private commissions, the quest for aesthetic objectivity, the rise of historic preservation, and the gradual transformation of controlled socialist nation-building into the violent nationalism of the 1990s.